2021
DOI: 10.1111/ajt.16465
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas transplantation from hepatitis C viremic donors to uninfected recipients

Abstract: There is a critical shortage of high-quality deceased donor organs to meet the demand of the waiting list. The current opioid epidemic has resulted in more organ donors due to drug overdoses, from 1.1% in 2000 to 13.4% in 2017, resulting in an overall increase in organ transplantation in the United States in the same time period. [1][2][3] It is notable that over 66% of drug overdose deaths occur in donors under 40 years of age. 1 Donors from drug overdoses are often ideal candidates for organ donation, given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Numerous studies have demonstrated the safety and efficacy of organ transplantation from HCV + donors to HCVrecipients. [6][7][8][9][10][11][12][13][14] Critical challenges remain to establish standard best practices that maximize benefit and minimize risk with the increased utilization of HCV + organs. Concerns for the feasibility of safely performing these transplants in "realworld" practice have been raised, leading some to suggest that these transplants should be restricted to sites running formal research protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the safety and efficacy of organ transplantation from HCV + donors to HCVrecipients. [6][7][8][9][10][11][12][13][14] Critical challenges remain to establish standard best practices that maximize benefit and minimize risk with the increased utilization of HCV + organs. Concerns for the feasibility of safely performing these transplants in "realworld" practice have been raised, leading some to suggest that these transplants should be restricted to sites running formal research protocols.…”
Section: Discussionmentioning
confidence: 99%
“…These studies yielded encouraging results 2,4 and have been followed by singlecenter reports of this practice in all solid organ types. [6][7][8][9][10][11][12][13][14] The overarching messaging from these reports is that transplanting HCV + donor organs into HCVrecipients is safe and that posttransplant cure of donor-derived HCV infection is nearly universal. The merits of this practice are notable: decreasing discards of otherwise excellent donor organs 15 and transplanting patients more quickly with grafts that appear to perform well.…”
Section: Introductionmentioning
confidence: 99%
“…Direct-acting antivirals (DAAs) reach high rates of sustained virological response (SVR) of more than 90%13 14 and have significantly impacted the pool of available organs for transplantation. The widespread use of DAA increased the number of transplant candidates, who are cleared of HCV, shortened their transplant waiting time and reduced their mortality rates 15–20. However, several reasons contribute to DAA treatment failure, such as genotype, treatment nativity and duration, non-adherence, drug–drug interactions (DDI), inadequate drug concentrations because of malassimilation and resistance-associated substitutions (RAS) 21.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of highly efficacious, pangenotypic direct‐acting antivirals (DAAs) for the treatment of hepatitis C virus (HCV) infection has allowed the safe transplantation of organs from HCV viremic (HCV+) donors (D) into HCV negative (HCV–) recipients (R) pool 1–5 . Since 2017, multiple clinical series have demonstrated the safety and efficacy of HCV+ to HCV– (HCV D+/R–) organ transplantation, with the cure rates for donor‐derived HCV infection approaching 100% 1,2,6–11 . However, significant adverse events such as fibrosing cholestatic hepatitis and acute rejection have been reported 12–15 .…”
Section: Introductionmentioning
confidence: 99%